Terapi Mindfulness (Meditasi Dzikir) terhadap Penurunan Insomnia pada Lansia - Bella Dara Anggun Pratiwi; Reni Chairani; Syamsul Anwar; Ferasinta Ferasinta (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to obtain an overview of mindfulness (dzikir meditation) on reducing insomnia in the elderly at the Tresna Werdha Social Home (PSTW) Bengkulu City. The quantitative using a quasi-experimental method, the research design used two groups pre-post test equivalent without control design. Sampling was done using the purposive sampling technique. Insomnia assessment instrument using the Jakarta Biological Psychiatry Study-Insomnia Rating Scale (KSPBJ-IRS). The results showed that the group that applied dzikir meditation got a p-value of 0,000 and the group without dzikir meditation got a p-value> 0.05. Multivariate test on insomnia in the pure intervention group experienced a decrease in insomnia with a p-value of 0.000. In contrast, there was no decrease in insomnia for the uninfected control group with a p-value> 0.05. In conclusion, there is a significant difference in reducing insomnia in the elderly before and after being given dzikir meditation intervention at the Tresna Wherda Social Institution (PSTW) Bengkulu City. Keywords: Insomnia, Elderly, Mindfulness (Meditas Dzikir)